Evaluation of Dimensional Accuracy of Master Models as a Function of Different Thickness of Wash Impression Material (Rapid) in Two Step Technique - M - Nili; K Rafighi (Isfahan University of Medical Sciences, 2006)
Introduction: Impression making is one of the most important steps in fixed prosthodontics. Due to contra-dictory opinions on the issue of the accuracy of silicone impression material as a function of technique, this study was carried out to assess the dimensional accuracy of master casts made by Rapid silicone material as a function of three impression techniques: with 2mm space, with 1mm space and without space for wash thickness.Methods and Materials: This experimental study was carried out by using laboratory models. Two dies (with and without undercut) served as laboratory models. 10 impressions were taken for each technique and stone models were poured. Six dimensions of 30 models (height and diameter for each die and distance between dies) were measured by digital caliper. The mean differences in measurements in stone model was compared with laboratory model. T-test and ANOVA analysis was used on statistical analysis.Results: Impression techniques with different amount of thicknesses of wash impression material had statistical significant effect on dimensional accuracy of master models.Conclusion: Impression technique with 2mm of space for wash material compared to impression technique with 1mm space and without space for wash material was more preferable.Key words: Impression technique, Wash-Putty, Impression materials, Dimensional accuracy, Space, Silicone.